EURASIAN ECONOMIC UNION: NEW STAGE OF ECONOMIC INTERACTION - Lyudmila F. Lebedeva; Tatyana E. Migaleva; Galina V. Podbiralina (Вестник Российского экономического университета имени Г. В. Плеханова, 2017)
The article analyzes the key national indicators of economic growth of country-members in the Eurasian Economic Union: Russia, Belorussia, Kazakhstan, Armenia, which covers 176 m of population and has GDP exceeding $ 4 trillion (by buying capacity). The article estimates the volume and extension of mutual economic ties. The role of Russia as a leading partner of the Union was demonstrated and priorities of cooperation for each country-member were identified.